Potentiation of sprint cycling performance: the effects of a high-inertia ergometer warm-up - Munro, L. A.; Stannard, S. R.; Fink, P. W.; Foskett, A. (Journal of Sports Sciences, 2014)
Participant and protocol factors affect post-activation potentiation response. Performance enhancement is more consistent in highly-trained participants following multiple sets of a biomechanically similar conditioning activity. Providing optimal conditions, 6 international-level sprint cyclists executed multiple sets of short maximal conditioning contractions on a high-inertia ergometer before metered sprint performance. Three trial conditions were completed on separate days after a standardised warm-up: dynamic (DYN: 4 × 4 crank-cycles), isometric (ISO: 4 × 5-sec maximal voluntary contraction (MVC)), and control (CON: rest). Performance was measured from standing start to maximum velocity on an inertial-load ergometer at baseline (Pre), 4 (Post4), 8 (Post8) and 16 (Post16) min post-conditioning. Performance and biomechanical measures were assessed across 4 sprint segments, with magnitude-based inferences used to assess the likelihood that any affect was beneficial. Performance time only improved in DYN Post4, a 3.9% reduction during the first crank cycle (92% likely). On the ascending limb of the power-cadence relationship, peak torque and average power increased by 6.2% (94% likely) and 4.0% (87% likely), respectively. In ISOPost16, optimal cadence increased (82% likely) and average power improved over the descending limb (76% likely). DYN and ISO potentiated extremities of the torque-cadence relationship at distinct recovery times post-conditioning. This study suggests merit in including a high-inertia warm-up for sprint cycling.